Do adolescents and young adults accessing the Emergency Room with substance use receive poor therapeutic indications at discharge? An observational retrospective study. Issue 12 (26th September 2021) - Molteni, Laura; Cafaro, Rita; Varinelli, Alberto; Espa, Irene; Mora Conde, Marian; Maria Brambilla, Anna; Viganò, Caterina; Dell'Osso, Bernardo
Abstract: Purpose: Emergency rooms (ERs) are usually the first point of contact with mental health services for adolescents with Substance Use Disorders (SUDs). However, only a minority of them receives proper treatment and follow‐up indications, increasing the risk of relapses and poor prognosis. In this perspective, we sought to characterize and compare socio‐demographic and clinical characteristics of adolescents with vs without SUDs accessing the ER, assessing potential differences in terms of discharge instructions. Methods: A sample of 557 ER accesses of patients aged 15‐25 years old in need of a psychiatric evaluation or with a psychiatric diagnosis at discharge was retrospectively analyzed. Patients were divided in two subgroups according to the presence of SUDs. Results: About 32.1% of patients had SUDs when accessing the ER. Among these, 62% were unknown to any psychiatric services and 57% were at their psychiatric onset. Nevertheless, considering discharge instructions, patients with current substance use received less therapeutic indication or were less frequently referred to psychiatric facilities, than those without substance use (57.8% vs 42.2%, P = .002). Conclusions: Substance abuse is strongly linked to psychopathology and ER accesses in young patients. However, we observed a large rate of SUDs patients unknown by any specialized mental health service, who received poor therapeutic and follow‐up instructions at discharge. Improving communication between ER operators and young patients with SUDs could longitudinally reduce the risk of addiction and related disability, morbidity and mortality.